Recent advances in the synthesis of TS-1 zeolite - Luan, Huimin; Xu, Cheng; Wu, Qinming; Xiao, Feng-Shou (Frontiers in chemistry, 2022)
Heteroatomic zeolites as an important class of zeolites, have been widely applied in industrially catalytic processes due to their unique properties. As one of the most representative heteroatomic zeolites, titanosilicate zeolites have been extensively used in the selective oxidations of organic substrates with H 2 O 2 such as cyclohexanone ammoximation, epoxidation of alkenes, and phenol hydroxylation. In this review, recent advances in the synthesis of TS-1 zeolite are briefly summarized, including use of low-cost raw materials (organic templates, silicon, and titanium sources), development of new synthesis routes (post-treatment synthesis, dry-gel conversion synthesis, solvent-free synthesis, and microwave-assisted synthesis), and new strategy for enhanced mass transfer in TS-1 crystals (synthesis of hierarchical and nanosized TS-1 zeolite). This review might help researchers to have a deep understanding on the synthesis of TS-1 zeolite and provide a new opportunity for the design and preparation of highly efficient TS-1 catalysts in the future.